Work Engagement in Indonesian Small and Medium Enterprises: A Bibliometric Analysis of Emerging Research Trends - Putra, Alfa Santoso Budiwidjojo (Kuras Institute, 2024)
This study aims to analyze the development of research on work engagement in Small and Medium Enterprises (SMEs) from 2020 to 2024 using a bibliometric approach. The method used is bibliometric analysis with the help of VOSviewer software for data visualization. Data was collected from the Dimensions database using the keywords